2011 IEEE Symposium on Computational Intelligence, Cognitive Algorithms, Mind, and Brain (CCMB) 2011
DOI: 10.1109/ccmb.2011.5952111
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis of left/right hand movement classification from EEG signal by intelligent algorithms

Abstract: Brain Computer interfaces (BCI) has immense potentials to improve human lifestyle including that of the disabled. BCI has possible applications in the next generation human-computer, human-robot and prosthetic/assistive devices for rehabilitation. The dataset used for this study has been obtained from the BCI competition-II 2003 databank provided by the University of Technology, Graz. After pre-processing of the signals from their electrodes (C3 & C4), the wavelet coefficients, Power Spectral Density of the al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
64
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 26 publications
0
64
0
2
Order By: Relevance
“…The expert uses the components with high LI to compose the set of features. Moreover, same spectral components used by [29,[45][46][47] to classify EEG signals are suggested as features. In order to reach a good spectral component resolution, a rectangular window was used, since it possesses the lower central lobe.…”
Section: Welch's Periodogram Componentsmentioning
confidence: 99%
“…The expert uses the components with high LI to compose the set of features. Moreover, same spectral components used by [29,[45][46][47] to classify EEG signals are suggested as features. In order to reach a good spectral component resolution, a rectangular window was used, since it possesses the lower central lobe.…”
Section: Welch's Periodogram Componentsmentioning
confidence: 99%
“…are investigated [5,7,9,10]. In some other studies, Radial Basis function (RBF) kernelized SVM classifier is introduced as a powerful tool that has the highest performance accuracy among LDA, K-Nearest Neighbor (KNN), Quadratic Discriminant Analysis (QDA) and SVM [5,7]. Moreover, experimental results demonstrated that the performance of classification in terms of time and accuracy increases when unimportant features are neglected [7].…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, some other features such as standard deviation, variance and power of signals are used widely for EEG signals [6]. In the literature, reducing the number of features is considered by using Principal Component Analysis (PCA) or Independent Component Analysis (ICA) [7,8]. However there is no need for feature reduction methods when wavelet transform is used because it produces optimal quantity of information.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations